Abusive drinking after liver transplantation is associated with allograft loss and advanced allograft fibrosis. Issue 12 (December 2013) - Rice, John P.; Eickhoff, Jens; Agni, Rashmi; Ghufran, Aiman; Brahmbhatt, Rinjal; Lucey, Michael R.
<x xml:space="preserve">Abstract</x> In patients who undergo liver transplantation for alcoholic liver disease (ALD), alcohol relapse is common. A return to abusive or excessive drinking likely decreases overall survival; however, the effects of alcohol use on allograft outcomes and histopathology are less well defined. We reviewed all cases of liver transplantation with ALD as an indication between January 1, 1995 and December 31, 2007. Allograft outcomes and histopathological results were compared for patients who relapsed into alcohol use and patients who maintained abstinence. Three hundred patients who underwent transplantation for ALD during this period survived at least 1 year, and 48 (16.0%) relapsed into alcohol use that came to clinical attention. The pattern of relapse was a single event for 10 patients (20.8%), intermittent relapses for 22 patients (45.8%), and continuous heavy drinking for 16 patients (33.3%). Continuous heavy drinking was associated with allograft loss in a univariate Cox proportional hazards analysis [hazard ratio (HR) = 2.43, 95% confidence interval (CI) = 1.26‐4.68, P = 0.008] and in a multivariate Cox proportional hazards regression (HR = 2.57, 95% CI = 1.32‐5.00, P = 0.006). A matched‐pair analysis that controlled for the hepatitis C virus status and the time to biopsy compared the results of allograft histopathology for patients who relapsed into alcohol use and patients who maintained abstinence. Significant steatosis [odds ratio (OR) = 3.46, 95% CI = 1.29‐9.31, P = 0.01], steatohepatitis (OR = 6.2, 95% CI = 1.70‐22.71, P = 0.006), and advanced (stage 3 or higher) fibrosis (OR = 23.18, 95% CI = 3.01‐177.30, P = 0.003) were associated with alcohol relapse. In conclusion, alcohol relapse after liver transplantation (particularly heavy drinking) is associated with decreased graft survival and advanced allograft fibrosis. Liver Transpl 19:1377‐1386, 2013. © 2013 AASLD.